2000
DOI: 10.1007/s002109900150
|View full text |Cite
|
Sign up to set email alerts
|

Co-regulation between cyclo-oxygenase-2 and inducible nitric oxide synthase expression in the time-course of murine inflammation

Abstract: Many in vitro studies have used cell cultures to focus on the relationships between cyclo-oxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) isoforms. We have investigated the time-course of regulation and the role of COX-2 and iNOS in a model of experimental inflammation in mice, the air pouch injected with zymosan. This study demonstrates that there is an early acute phase (4 h) mediated mainly by eicosanoids, with high levels of prostaglandin E2 (PGE2) produced by cyclo-oxygenase-1. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
1
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(136 citation statements)
references
References 55 publications
6
126
1
3
Order By: Relevance
“…Although the present investigation cannot establish the mechanism of interaction between NOS and COX activity, the possible mechanism is that inhibition of NO by GJE glycoprotein influence the COX-2 activity, thus may modulate the inflammation. Further, it is reported earlier that NO can stimulate COX activity via its reaction with heme component of the COX enzyme [31,32]. Accumulating evidence has suggested that the gene expression of iNOS and COX-2 can be also regulated by several transcription factors such as nuclear factor interleukin-6 (NF-IL6), FOS/JUN, CCAAT/enhancer-binding protein (C/EBP), and nuclear factor kappa B (NF-jB) [11,12].…”
Section: Discussionmentioning
confidence: 96%
“…Although the present investigation cannot establish the mechanism of interaction between NOS and COX activity, the possible mechanism is that inhibition of NO by GJE glycoprotein influence the COX-2 activity, thus may modulate the inflammation. Further, it is reported earlier that NO can stimulate COX activity via its reaction with heme component of the COX enzyme [31,32]. Accumulating evidence has suggested that the gene expression of iNOS and COX-2 can be also regulated by several transcription factors such as nuclear factor interleukin-6 (NF-IL6), FOS/JUN, CCAAT/enhancer-binding protein (C/EBP), and nuclear factor kappa B (NF-jB) [11,12].…”
Section: Discussionmentioning
confidence: 96%
“…Some studies suggested that COX-1 is the major source of PG during inflammation (36,37), whereas others suggested that the PGs that contribute to inflammatory responses are derived exclusively from COX-2 (11,38). Other investigators have dissected the inflammatory response in two phases: an early phase (4 h) mediated by COX-1-generated PG, and a later phase (after 12 h) mediated by COX-2-derived PG (39). Thus, both COX-1 and COX-2 synthesize PG during the inflammatory response, but the relative contribution of one or the other isoform depends on the a Results are expressed as mean Ϯ SEM.…”
Section: Characterization Of Nos and Cox Isoform Expression And Endprmentioning
confidence: 99%
“…Pro-inflammatory cytokines, such as TNF-α, IL-1β and IL-6, are potentially capable of injuring host tissues to play key homeostatic functional roles (Laskin and Pendino, 1995). NO and PGE 2 are generated by the inducible isoforms of NO synthase (iNOS) and cyclooxygenase-2 (COX-2) (Posadas et al, 2000). NO is essential for host innate immune responses to pathogens, and for the regulation of other physiological functions including neurotransmission, vasodilatation, and neurotoxicity (MacMicking et al, 1997).…”
Section: Introductionmentioning
confidence: 99%